Meningkatkan Prestasi Perbankan Melalui Alokasi Dana Pendidikan Pada Bank PD. BPR Sarimadu Kabupaten Kampar - Arman, Arman (Jurnal Daya Saing, 2015)
Abstract: This research is motivated by the education cost allocation policy by this company, the problems that occurred allocation of education costs unstable that threaten the sustainability of educational activities for employees. Based on the theory that education affects performance, but what about the presence of unstable budget allocations for education, whether affecting employee performance at work. Quantitative research using time series data for the year 2003 to the year 2013 and analyzed using simple linear regression. Based on the research result shows that the allocation of the cost of education proved to have a significant influence on employee performance Bank PD. RB Sarimadu Kampar district (3,155> 2,228) are shown on the company's revenues continue to increase. in order to improve employee performance and in turn is raise the performance of the company, then the company needs to allocate the cost of education and the increasing cost of education and create a stable allocation of the cost of education by way of budgeting as fixed costs in the company's budget. Keywords : Cost of Education and Job Performance